A demographic analysis of UK adventure sports coaches. Issue 1 (2nd January 2022) - Christian, Ed; Kelly, John S.; Piggott, Lucy V.; Hoare, James
ABSTRACT: The role of the Adventure Sports Coach (ASC) has recently become the focus of academic interest. Although research emerging from the field is beginning to diversify, the majority is limited in terms of sampling and methodology. The current study broadened the participant base by providing a demographic analysis of ASCs. An online survey of 504 participants captured key demographics, 'coaching category' and 'coaching level'. Chi-square analysis investigated differences between genders. ASCs were predominantly male, relatively young, well-educated and well qualified. Despite many coaches holding high-level awards, their main practice was coaching beginners. A marked asymmetry existed between genders, with two-thirds of the sample being male. Female coaches were younger, less well qualified, and significantly under-represented in the higher coaching echelons. The lack of female coaches, and their clear under-representation in higher coaching categories is concerning. Recruitment, retention, and development of female ASCs is therefore a priority.